Childhood and adolescent obesity and long‐term cognitive consequences during aging. Issue 5 (26th December 2014) - Wang, Jun; Freire, Daniel; Knable, Lindsay; Zhao, Wei; Gong, Bing; Mazzola, Paolo; Ho, Lap; Levine, Samara; Pasinetti, Giulio M.
ABSTRACT The prevalence of childhood/adolescent obesity and insulin resistance has reached an epidemic level. Obesity's immediate clinical impacts have been extensively studied; however, current clinical evidence underscores the long‐term implications. The current study explored the impacts of brief childhood/adolescent obesity and insulin resistance on cognitive function in later life. To mimic childhood/adolescent obesity and insulin resistance, we exposed 9‐week‐old C57BL/6J mice to a high‐fat diet for 15 weeks, after which the mice exhibited diet‐induced obesity and insulin resistance. We then put these mice back on a normal low‐fat diet, after which the mice exhibited normal body weight and glucose tolerance. However, a spatial memory test in the forms of the Morris water maze (MWM) and contextual fear conditioning at 85 weeks of age showed that these mice had severe deficits in learning and long‐term memory consolidation. Mechanistic investigations identified increased expression of histone deacetylases 5, accompanied by reduced expression of brain‐derived neurotrophic factor, in the brains 61 weeks after the mice had been off the high‐fat diet. Electrophysiology studies showed that hippocampal slices isolated from these mice are more susceptible to synaptic impairments compared with slices isolated from the control mice. We demonstrated that a 15‐week occurrence of obesity and insulin resistance during childhood/adolescence induces irreversible epigenetic modifications in the brain that persist following restoration of normal metabolic homeostasis, leading to brain synaptic dysfunction during aging. Our study provides experimental evidence that limited early‐life exposure to obesity and insulin resistance may have long‐term deleterious consequences in the brain, contributing to the onset/progression of cognitive dysfunction during aging. J. Comp. Neurol. 523:757–768, 2015. © 2014 Wiley Periodicals, Inc.